CONVERTING THEORY AND WAR DOCTRINE TO REALISTIC TRAINING FOR ENSURING THE SUCCESS OF MILITARY CAMPAIGN PLANNING - Alok Ahlawat; Bahaizil Nazim B. Mohd Bakar; Steven Barter; Fahad B. Al Subaie; Steven O’Hara; Caleb Slayton (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2018)
Military campaigns in the 21st Century are extremely complex multi-dimensional undertakings. In today’s globalized reality, influence of wars will go beyond the theatre of operations into issues of international economy, human migration, airspace and sea lanes, thus adding new dimensions to campaign planning.  Converting theory and doctrine to practice is never easy.  Realistic training may be the best bridge to ensure that classroom knowledge is correctly applied to the real battlefield.  This paper looks at this challenge through the combined experience of six foreign exchange students who graduated from Indonesia’s Air Command and Staff College, 2018.  The purpose of this paper is to highlight some of the challenges to campaign planning, especially in light of multinational influences, extract lessons learned from recent military campaigns and then provide feedback for Indonesia’s wargaming training methodology as practiced in the air command and staff college.  The foundation to Indonesia’s wargaming exercises is the 14-step Military Decision Making Process (MDMP).  MDMP in its general form is part of the campaign planning processes for the authors’ respective countries too, varying only in the sequence and emphasis on steps and tasks within the process and strategies for exercising the process.  This paper will conclude that even the most theoretically sound campaign planning process would lead to operational failure, unless critical thinking & planning abilities are developed in upcoming military leaders through a sound understanding of theory, realistic wargaming, and deep analysis. This requires realistic training in an open learning environment, and a willingness to analyse one’s own country-specific mistakes and successes.